Modification of Modern Coconut Peeling Processing Using Appropriate Technology to Enhance Farmer Productivity in Balleanging Village, Bulukumba: Modifikasi Pengolahan Pengupas Kelapa Modern Berbasis Teknologi Tepat Guna untuk Meningkatkan Produktivitas Petani di Desa Balleanging Bulukumba - Gusnawati*, Gusnawati; Arman, Muh; Mahmuddin, Mahmuddin; azis, Hijrah Amaliah; Selviani, Selviani; Akhyar, Khaeril; Fahri, Fadil (Universitas Lancang Kuning, 2025)
This community service activity examines the implementation of modern coconut husking technology and coconut husk waste utilization in Balleanging Village, Ujung Loe District, Bulukumba Regency, through the Community Partnership Program (PKM). The research focuses on the Jaya Abadi Farmer Group, consisting of 30 farmers with average land ownership of 0.5-1.5 hectares. The methodology includes location surveys, intensive 4-week training, technology implementation, and program evaluation. Results show significant productivity improvements, with husking capacity increasing from 12-60 to 200 coconuts per hour, reducing processing time per unit from 1-5 minutes to 0.3 minutes, achieving 94% efficiency. Modern technology implementation also reduced labor requirements by 50-67% and minimized workplace accident risks. The coconut husk waste processing education program resulted in the diversification of economically valuable products such as cocopeat, cocofiber, and planting media. Program evaluation demonstrates high technology adoption rates, supported by a comprehensive assistance system covering operational aspects, maintenance, and product development. This technological transformation not only enhances production efficiency but also creates opportunities for sustainable economic development through value-added waste utilization, positively impacting the welfare of coconut farmers in Balleanging Village.